Pelatihan Speaking Skills untuk Massage Therapists Putri Kedaton Griya SPA Sleman DIY - Ali Satia Graha; Titis Dewi Cakrawati; Sri Sundari; Danny Eka Wahyu Saputra; Ahmad Ridwan (Dharma Vritta Vokasional, 2025)
This community service activity aims to improve the English-speaking skills of massage therapists at Putri Kedaton Griya SPA in Sleman, Special Region of Yogyakarta. The training is crucial to help therapists communicate effectively with foreign guests utilizing spa services. The training was conducted using interactive methods, including conversation practice, spa-related vocabulary, and guest service simulations. The results of this activity indicate a significant improvement in the therapists’ speaking skills, particularly in the use of common phrases and polite responses when interacting with guests. Additionally, the therapists’ confidence in using English increased, contributing to an overall enhancement in service quality.